2017
DOI: 10.1057/s41599-017-0023-2
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic responsibility as an edifying force in academic research: investigating the moral challenges and opportunities of an impact agenda in the UK and Australia

Abstract: The requirement to anticipate, articulate and evaluate the impact of research is a growing part of academic labor. A research impact agenda in the UK and Australia reflects a drive from Governments to see a return on the public investment of research. Some view this as symptomatic of a marketised higher education system, in which knowledge is a commodity as opposed to an object of intrinsic value and dismiss the latter view as nostalgic and unrealistic. Within a research context where knowledge continues to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 23 publications
0
35
1
Order By: Relevance
“…Study participants also outlined a range of ways in which working in the Baltic Eye Project has impacted them as individuals, for example, via increased job satisfaction. Interestingly, this result contrasts recent perception studies of academics from diverse disciplines that found growing scepticism towards the impact agenda [ 53 , 54 ]. The sense of job satisfaction reported by participants arose from the learning opportunities associated with working in a diverse team, as well as a sense of personal achievement from observing tangible impacts of science on policy and practice.…”
Section: Discussioncontrasting
confidence: 97%
“…Study participants also outlined a range of ways in which working in the Baltic Eye Project has impacted them as individuals, for example, via increased job satisfaction. Interestingly, this result contrasts recent perception studies of academics from diverse disciplines that found growing scepticism towards the impact agenda [ 53 , 54 ]. The sense of job satisfaction reported by participants arose from the learning opportunities associated with working in a diverse team, as well as a sense of personal achievement from observing tangible impacts of science on policy and practice.…”
Section: Discussioncontrasting
confidence: 97%
“…Acknowledging that making science more accessible is difficult, Language Learning aims to help researchers fulfill a sense of epistemological duty to share the knowledge they establish (Chubb & Reed, ). We also hope that this initiative partially addresses our ethical, moral, and social responsibilities to the research participants who provide data and who, directly or indirectly, fund our work.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the importance of need satisfaction at work was elegantly demonstrated by Olafsen, Halvari, Forest, and Deci (2015), who found that workplace psychological need satisfaction related to more internal, or personally driven, motivations to work, whereas merely incentivising employees with money did not. Overall, these findings highlight the role of need satisfaction in the workplace context, but they have rarely been extended to understand the experiences of those working in HE (for an exception, see Chubb & Reed, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…In light of this, many commentators also note the positive aspects of the REF. Here, the REF provides a necessary accountability mechanism for the annual allocation of around £1.6 billion of flexible public funding, can inspire positive changes in the UK's academic culture (such as encouraging more impactful work that benefits society) and effectively harnesses academic epistemic responsibilities (Chubb & Reed, 2017; Hill, 2016; Oancea, 2019).…”
Section: Introductionmentioning
confidence: 99%